Salivary levels of cariogenic bacterial species during orthodontic treatment with thermoplastic aligners or fixed appliances: a prospective cohort study - Iosif Sifakakis; William Papaioannou; Aikaterini Papadimitriou; Dimitrios Kloukos; Spyridon N. Papageorgiou; Theodore Eliades (SpringerOpen, 2018)
Abstract Background Fixed orthodontic appliances might be associated with intraoral adverse effects on enamel, due to plaque accumulation and their colonization by oral microbes. At the same time, the demand for esthetic alternatives to orthodontic treatment, like thermoplastic aligners, is growing. However, thermoplastic aligners may behave differently intraorally than fixed appliances in terms of bacterial colonization and biofilm formation. Therefore, the aim of this prospective cohort study was to assess the salivary prevalence of the cariogenic bacteria Streptococcus mutans, Lactobacillus acidophilus, and Streptococcus sanguinis among adolescents treated orthodontically with thermoplastic aligners or fixed appliances. Methods Thirty adolescent patients (17 girls/13 boys; mean age 13.8 years old) were assigned to treatment with either (i) self-ligating fixed appliances with nickel-titanium archwires or (ii) aligners constructed from clear transparent polyethylenterephthalat-glycol copolyester (PET-G) thermoplastic sheets. Whole stimulated saliva was collected from each patient at three time points: at baseline (before bonding and initiation of orthodontic therapy or before insertion of the thermoplastic aligners), after 2 weeks, and after 1 month. A simplified plaque index, a simplified gingival index, and the decayed, missing, and filled teeth (DMFT) index were assessed from the clinical examination of the patients. Microbiological analysis of salivary bacteria was performed by quantitative polymerase chain reaction, followed by descriptive and inferential statistics at the 5% level. Results Although patients treated with aligners had significantly lower plaque and gingivitis scores throughout treatment compared to patients treated with fixed appliances, no significant difference could be found between the S. mutans counts of the two groups at any time through treatment (P > 0.05). On the other hand, patients treated with aligners had significantly lower salivary S. sanguinis counts at all time points than patients treated with fixed appliances (P < 0.05). Finally, almost no L. acidophilus were identified in the collected saliva samples in either of the treated samples. Conclusions Within the limitations of this study, there were no differences in the salivary counts of S. mutans or L. acidophilus among adolescent patients treated for 1 month with thermoplastic aligners or self-ligating appliances. On the other hand, patients treated with aligners had lower salivary levels of S. sanguinis compared to those treated with self-ligating appliances.